Filling the gap A microscopic zooarchaeological approach to changes in butchering technology during the Early and Middle Bronze periods at Tall Zirā´a, Jordan - Greenfield, Haskel J. 1957-; Beller, Jeremy A.; Gaastra, Jane S.; Vieweger, Dieter 1958- (2023)
The Early Bronze Age (3500–2000 bce) of the southern Levant experienced the development of bronze metal technology, but the rate and nature of its dissemination beyond the elite are unclear. In the southern Levant and elsewhere, based upon the microscopic analysis of butchering marks, it has been proposed that bronze slicing tools only begin to be used in quantities in the Middle Bronze. However, previous analyses have always lacked data sets from the Early Bronze IV/Middle Bronze I period (c. 2500–2000 bce). In this paper, we present the butchered animal bone data from the site of Tall Zirā´a (in the NW corner of Jordan) where there is a fuller chronological sequence for the Early and Middle Bronze Ages. These data provide a unique opportunity to investigate long-term changes in butchering practices in the southern Levant. The analysis demonstrates that the new (bronze) technology does not seem to be integrated into quotidian activities, such as the processing of animal carcasses, until well into the Middle Bronze Age (MB IIB). Until then, and in subsequent phases of the MB, the majority of butchering marks are made by stone implements.